How political malpractice affects trust in EU institutions. Issue 4 (6th June 2020) - van Elsas, Erika J.; Brosius, Anna; Marquart, Franziska; De Vreese, Claes H.
Abstract: Political misconduct is known to harm the politicians involved. Yet, we know less about how such events affect trust in political institutions. We study a real-world political malpractice affair in the European Commission, using a three-wave panel design to investigate how information about the affair influences trust in EU institutions. This enables us, first, to isolate the impact of new information on political trust, remedying endogeneity issues common in political trust research. Second, we assess which institutions are affected most ( specificity ) and whether effects depend upon citizens' sophistication levels ( conditionality ). Finally, we assess the durability of effects over time. Our findings demonstrate that citizens obtain knowledge about EU affairs through the media, and use this knowledge in their trust evaluations. In doing so, citizens differentiate between EU and national institutions, with trust in the European Commission affected most. This suggests a sophisticated process and highlights the evaluative nature of political trust.